Planetary Health Rounds: A novel educational model for integrating healthcare sustainability education into postgraduate medical curricula - Tajdeep Brar; Jordana Compagnone; Sanjana Sudershan; Maryam Yunus; Loukman Ghouti; Allen Tran; Joffre Munro; Babar Haroon; Nabha Shetty (The Journal of Climate Change and Health)
Introduction: Climate change poses a major threat to public health, necessitating significant reductions in greenhouse gas (GHG) emissions to limit its effects. The healthcare sector itself is a significant contributor to GHG emissions, particularly in high-income countries such as Canada and the United States. Providing medical learners with education on this topic has been identified as an important component of efforts to reduce GHG emissions; however, there is a lack of tools available both for providing education on healthcare sustainability, and for integrating this topic into postgraduate medical curricula. Case Presentation: The Planetary Health Rounds are an educational initiative aimed at integrating climate change concepts and healthcare sustainability into the Internal Medicine residency curriculum, using a case-analysis format in conjunction with the open-source HealthcareLCA Database (https://healthcarelca.com/database), a living repository of data on healthcare-associated GHG emissions. Methods: Learners conduct a case analysis of an internal medicine patient and estimate the total emissions associated with their admission, which they then present at an end-of-rotation teaching session, with discussions centering on the link between climate change and health as well as reducing emissions. Discussion: The Planetary Health Rounds, implemented in 2023, have been well-received by trainee physicians despite some challenges having been encountered. These include service demands impacting participation, a lack of emissions data for internal medicine-related care, issues with the generalizability of said data, and consistent access to a planetary health expertise during rounds. Conclusion: This initiative provides a novel way of incorporating teaching on climate change and health into postgraduate training curriculums.